PEMANFAATAN RUANG TERBUKA HIJAU PUBLIK DI KECAMATAN LEMBAH SEGAR KOTA SAWAHLUNTO - Arizandi, Alfredi (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to determine the use of public green open space in Lembah Segar District, Sawahlunto City. The research method used in this research is descriptive qualitative method. The type of data used in this study consisted of primary data and secondary data. Sources of primary data obtained from interviews, documentation and surveys. The existence of public green open space for urban communities affects the comfort level of the community, this can be seen from several indicators that support the level of community comfort, such as the level of visits, infrastructure, and employment. However, judging from what is in the field, there are places where there should be no residential buildings, such as locations that should be urban forests but are used as residential locations.